Systematic review on T3 laryngeal squamous cell carcinoma; still far from a consensus on the optimal organ preserving treatment. Issue 1 (January 2017) - Riga, M.; Chelis, L.; Danielides, V.; Vogiatzaki, T.; Pantazis, T.-L.; Pantazis, D.
Abstract: Objective: The optimal treatment of patients with T3 laryngeal carcinoma is controversially challenged by open partial laryngectomies (OPL), transoral laser microsurgery (TLM) and radiation therapy alone (RT) or combined with chemotherapy (ChRT). Treatment guidelines, experts' opinions and clinical studies are highly contradictory. The aim of this study is to compare the primary outcomes of the available treatment methods and identify the sources of variance among studies. Methods: A review of the literature published in the time period 2003–2015 was conducted via the PubMed database (www.pubmed.org ) and Scopus database (www.scopus.com ) with the search terms "T3 laryngeal squamous cell cancer treatment". Data from clinical studies involving patients with T3 laryngeal cancer (n > 10) subjected to TLM, OPL, ChRT or RT, were pooled. In the absence of controlled studies, prospective and retrospective clinical trials with minimum 5-year follow-up were acceptable, provided that they included a description of patient eligibility criteria, so as to exclude studies with serious selection bias. Results: Literature lacks studies with homogenous populations regarding TNM staging, preoperative/postoperative treatment or anatomical subsite. This raises substantial controversies and prohibits the conduction of a meta-analysis. Data for qualitative analysis were pooled from 8 studies (n = 1226). OPL and TLM both offer patients high survival and organ preservation rates. Preoperative induction chemotherapy seems to significantly compromise overall survival. Conclusions: Multicenter studies referring to homogenous populations, at least regarding staging and anatomical subsite, are needed. No safe conclusions can be drawn given the heterogeneity in patient cohorts, study design and evaluation of results in the existing literature.